The Covered Wagon Based on a Novel by Emerson Hough - Cruze, James; Brown, Karl; Kerrigan, J. Warren; Wilson, Lois; Torrence, Ernest (Paramount Pictures, 1990)
In 1848, two men (Charles Ogle and J. Warren Kerrigan) lead a pair of lengthy wagon trains towards Oregon while Ogle’s daughter (Lois Wilson) struggles between loyalty to her fiance (Alan Hale) and her growing interest in Kerrigan, whose checkered history causes her concern. Director James Cruze helmed this remarkably authentic recreation of the westward movement in American history, which distinguishes itself almost immediately as a film worthy of our attention. [filmfanatic.org]